Answer:
Step-by-step explanation:
Hope this helped!
<h3>~AH1807</h3>
Answer:
11.6 miles
Step-by-step explanation:
Given that:
Distance from J2 to J3 = 8.7 miles
Distance between J1 and J2 = 1/3 of J2 toJ3
Hence, distance between J1 and J2 becomes :
1/3 * 8.7 miles = 2.9 miles
Distance from J1 to J3 equals :
(J1 to J2) + (J2 to J3)
2.9 miles + 8.7 miles
= 11.6 miles
Answer:
Step-by-step explanation:
x2 - 4x - 12 = 0
x2 - 6x + 2x - 12= 0
x(x - 6) + 2(x - 6) = 0
x + 2 = 0
x = - 2
x - 6 = 0
x = 6
Answer:
Step-by-step explanation:
no cause 2/10 is the same as 20/100
Hi there!
To solve this equation, we can use distributive property.
I listed the terms you have to multiply :
x² × x² = x^4
x² × 2x = 2x³
x² × 5 = 5x²
2x × x² = 2x³
2x × 2x = 4x²
2x × 5 = 10x
-1 × x² = -x²
-1 × 2x = -2x
-1 × 5 = -5
Add all of them....
x^4 + 2x³ + 5x² +2x³ + 4x² + 10x - x² - 2x - 5
add up the like terms to simplify
x^4 + 4x³ + 8x² + 8x - 5
Hope this helped! :)